Complications associated with long‐term positive‐pressure ventilation in dogs and cats: 67 cases. Issue 3 (10th January 2022) - Cagle, Laura A.; Hopper, Kate; Epstein, Steven E.
Abstract: Objectives: To determine the complications associated with positive‐pressure ventilation (PPV) in dogs and cats. Design: Retrospective study from October 2009 to September 2013. Setting: University Teaching Hospital. Animals: Fifty‐eight dogs and 9 cats. Measurements and main results: Medical records were retrospectively reviewed; signalment, complications associated with PPV, duration of PPV, and outcome were recorded. Complications most commonly recorded during PPV included hypothermia 41/67 (61%), hypotension 39/67 (58%), cardiac arrhythmias 33/67 (49%), a positive fluid balance 31/67 (46%), oral lesions 25/67 (37%), and corneal ulcerations 24/67 (36%). A definition of ventilator‐associated events (VAE) extrapolated from the Center of Disease Control's criteria was applied to 21 cases that received PPV for at least 4 days in this study. Ventilator‐associated conditions occurred in 5 of 21 (24%) of cases with infection‐related ventilator‐associated conditions and ventilator‐associated pneumonia identified in 3 of 21 (14%) cases. Conclusions: Complications are common and diverse in dogs and cats receiving long‐term PPV and emphasizes the importance of intensive, continuous patient monitoring and appropriate nursing care protocols. Many of the complications identified could be serious without intervention and suggests that appropriate equipment alarms could improve patient safety. Development of veterinary specific surveillance tools such as the VAE criteria would aid future investigations and allow for effective multicenter studies.